Enhancing Data Visualization Competencies Through Power BI Training - Agwil, Winalia; Sunandi, Etis; Rizal, Jose; Faisal, Fachri; Nugroho, Sigit; Syahada, Sri; Hermalia, Hermalia (Research Collaboration Community (RCC), 2025)
Vocational High School (SMK) aims to prepare students with the skills and knowledge required to meet industry demands. Recognizing the importance of data analysis and visualization in the workforce, this community service focuses on enhancing these competencies among SMKN 04 Kota Bengkulu students, particularly those in the Software Engineering program. A community service program was conducted to train students in utilizing Power BI for real-time and interactive data visualization. The training program included preparatory surveys, module development, and practical workshops. Students actively participated, demonstrating a greater interest and understanding of data visualization concepts. Evaluation results showed that 89% of participants found the training beneficial, and 84% mastered Power BI’s visualization techniques. The outcomes highlight the program's effectiveness in equipping students with industry-relevant skills, emphasizing the need for similar initiatives targeting broader student groups. This project bridges the gap between vocational education and the digital economy's demands.